Development of Agribusiness-Based Capture Fisheries Subsector in Coastal Areas in Buton Tengah Regency, Southeast Sulawesi (Asset Approach and Problem Analysis) - Jabuddin, La Ode; Abdi, Abdi; Astarika, Rina (Pascasarjana Universitas Halu Oleo, 2024)
In the development plan for the capture fisheries subsector, at least two resources are the basis for its development, namely production potential and human resource potential (fishermen). This research aims to analyze the potential for developing the capture fisheries subsector using an asset approach and problem analysis, as well as formulating program plans and follow-up actions for the development of the capture fisheries subsector in Buton Tengah Regency. The analytical method in this research uses a potential (asset) analysis approach and a problem analysis approach, where the informants are relevant stakeholders who are considered to know the root of the problem in the development of capture fisheries commodities in Buton Tengah Regency. The research results show that: (1) the development of the capture fisheries subsector in Buton Tengah Regency has prospects for development, as indicated by a location quotient (LQ) value of greater than one (1.07), (2) Development of the capture fisheries subsector using a problem analysis approach has five main threats, namely: limited access to capital for fishermen, limited fishing anchorage areas, fish storage that does not last long, monopoly of production prices by intermediaries, and sources of financing dominated by intermediaries, (3) Formulation of program plans and follow-up in the development of the capture fisheries subsector can be carried out through training activities and technical guidance, counseling, procurement of fleets and modern fishing equipment, capital assistance and facilities, promotions, construction of fish auction sites, as well as the revitalization of fishermen's cooperative management. Therefore, synergy and high commitment from all stakeholders are highly expected to resolve various problems in the development of captured fisheries commodities in Buton Tengah Regency.